Cost-Consequence Analysis of Three Different Diagnostic Strategies in the First- and Second-Line Treatment of Locally Advanced or Metastatic Non-Small-Cell Lung Cancer - Gancitano, Giovanni; Ravasio, Roberto; Dionisi, Matteo; Cortinovis, Diego (Farmeconomia. Health economics and therapeutic pathways, 2018)
BACKGROUND: Unlike the tissue one, liquid biopsy is a less invasive diagnostic method for the assessment of possible mutations of the tumor, based on the analysis of circulating free DNA (cfDNA) present in the plasma component of the blood. Because blood samples are easily obtainable, plasma biopsy is a non-invasive method, supplementing the more traditional biopsy techniques. AIM: A cost-consequence analysis was conducted to compare the adoption of three different diagnostic strategies in the first- and second-line treatment of locally advanced or metastatic NSCLC: i) tissue strategy (only tissue biopsy for first and second line), ii) combined strategy (first line: tissue biopsy. If unknown, liquid biopsy; second line: liquid biopsy. If negative, tissue biopsy) and iii) potential strategy (first line: tissue biopsy. If unknown or tissue ineligible, liquid biopsy; second line: liquid biopsy. If negative, tissue biopsy). METHODS: A decision-analytic model was developed considering the Italian NHS’s perspective. We only evaluated direct medical costs (tissue biopsy, management of complications associated with tissue and liquid biopsies) borne by the NHS. The CCA was conducted over a time horizon of 1 year, assuming that for each patient with mNSCLC the diagnostic pathway (first- and second-line treatment) ended within such period. Key variables were tested in the sensitivity analysis. RESULTS: Considering both the first and the second line of treatment, the potential strategy constitutes the cost-effective alternative, characterized by an average cost per correctly identified case (€ 685) lower than that estimated for the combined strategy (€ 732) or for the tissue strategy (€ 1,004). The potential strategy remains cost-effective, also considering the results referred to the first- or second-line treatment only. CONCLUSION: The choice of a correct diagnostic strategy is crucial in order to optimize cancer therapies in the first- and second-line treatment of locally advanced or metastasized NSCLC. The addition to the diagnostic pathway of the liquid biopsy would correctly identify a greater number of cases, supporting the prescription of the best oncological therapy.